Heat Equations Associated with Weinstein Operator and Applications. (7th October 2013) - Mejjaoli, Hatem
Abstract : We establish a characterization for the homogeneous Weinstein-Besov spaces via the Weinstein heat semigroup. Next, we obtain the generalized Sobolev embedding theorems.